The perspectives of rehabilitation medical professionals of an Indian apex tertiary care hospital - Saha, Vasundhara; Mallik, Kanhu C. (International Journal of Research in Medical Sciences, 2021)
Background: Spiritual care has been considered one of the components of rehabilitation. But its study and applicability is considerably lacking amongst the rehabilitation professionals. The purpose of this study was to identify the barriers in addressing spiritual issues of patients and understanding the perceptions of rehabilitation professionals in order to inculcate a bio-psycho-socio-spiritual model of care. Methods: In this cross sectional survey, 35 rehabilitation medical professionals at our institute completed a questionnaire assessing their opinion about religion, and spirituality with its inclusion in clinical practice & medical education. The individual domains were analyzed through descriptive statistics. Results: The findings suggested that most rehabilitation professionals understand the importance of addressing spiritual issues of patients but lack its feasibility in clinical practice due to multiple barriers, mainly due to lack of time, training, knowledge, fear of imposing religious beliefs and failing to differentiate between religion and spirituality. Conclusions: The lacuna in various dimensions imposes restrictions in imparting spiritual care to patients. It may affect the total care and thus quality of life of such patients. This can be addressed by proper training and sensitization of medical professionals during medical education as well as during clinical practice.